Synthesis of disubstituted furans catalysed by [(AuCl)2(μ-bis(phosphino)metallocene)] and Na[BArF24]. Issue 44 (27th October 2022) - Gwinn, Reilly K.; Boggess, Anna E.; Winter, Elizabeth P.; Nataro, Chip
Abstract : Two new gold compounds with bis(phosphino)metallocene ligands were prepared and characterized by NMR and X-ray crystallography. These and related compounds are catalysts in formation of disubstituted furans from terminal alkynes and pyridine- N -oxide. Abstract : The catalytic activity of a series of [(AuCl)2 (μ-PP)] (PP = 1, 1′-bis(phosphino)metallocene ligands) compounds in the presence of Na[BArF24 ] (BArF24 = tetrakis(3, 5-bis(trifluoromethyl)phenyl borate)) was examined in the formation of disubstituted furans from pyridine- N -oxide and terminal alkynes. The products of these reactions were typically the 2, 5-disubstituted furans, but in the case of using 2-ethynylpyridene, the 2, 4-disubstituted furan formed. The catalytic efficiency was dependent upon both the nature of the terminal alkyne and the 1, 1′-bis(phosphino)metallocene ligands. During the course of this study, two new compounds, [(AuCl)2 (μ-dppr)] and [(AuCl)2 (μ-dppo)] (dppr = 1, 1′-bis(diphenylphosphino)ruthenocene; dppo = 1, 1′-bis(diphenylphosphino)osmocene), were prepared and characterized by NMR. X-ray crystal structures of both compounds were determined and the oxidative electrochemistry of these new compounds was examined.